Can You Solve This Question Without Using L'Hopital's Rule?

Calculus Level 3

Let g g be the function g ( x ) = e 2 x + 1 g\left(x\right)=e^{2x+1} for all real x x . Then lim x 0 g ( g ( x ) ) g ( e ) x = \displaystyle \lim_{x \to 0} \frac{g\left(g\left(x\right)\right)-g\left(e\right)}{x} =

4 e 2 4e^2 4 e 2 e + 2 4e^{2e+2} 2 e 2 e + 1 2e^{2e+1} e 2 e + 1 e^{2e+1} 2 e 2e

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

= lim x 0 g ( g ( x ) ) g ( e ) x \displaystyle = \lim_{x \to 0} \frac{g\left(g\left(x\right)\right)-g\left(e\right)}{x}

= lim x 0 g ( g ( x ) ) g ( g ( 0 ) ) x 0 \displaystyle = \lim_{x \to 0} \frac{g\left(g\left(x\right)\right)-g\left(g\left(0\right)\right)}{x-0}

= lim x 0 g ( g ( x ) ) g ( g ( 0 ) ) g ( x ) g ( 0 ) g ( x ) g ( 0 ) x 0 \displaystyle = \lim_{x \to 0} \frac{g\left(g\left(x\right)\right)-g\left(g\left(0\right)\right)}{g\left(x\right)-g\left(0\right)}\cdot\frac{g\left(x\right)-g\left(0\right)}{x-0}

When x 0 x \to 0 , g ( x ) g ( 0 ) = e g(x) \to g(0) = e

= lim g ( x ) e ( g ( g ( x ) ) g ( e ) g ( x ) e ) lim x 0 ( g ( x ) g ( 0 ) x 0 ) \displaystyle = \lim_{g(x) \to e} \left(\frac{g\left(g\left(x\right)\right)-g\left(e\right)}{g\left(x\right)-e}\right)\cdot \lim_{x \to 0} \left(\frac{g\left(x\right)-g\left(0\right)}{x-0}\right)

= g ( e ) g ( 0 ) \displaystyle = g'\left(e\right)\cdot g'\left(0\right)

= 4 e 2 e + 2 \displaystyle = \boxed{4e^{2e+2}}

Brian Moehring
Aug 19, 2018

By the definition of the derivative, lim x 0 g ( g ( x ) ) g ( e ) x = lim x 0 ( g g ) ( x ) ( g g ) ( 0 ) x 0 = ( g g ) ( 0 ) = g ( g ( 0 ) ) g ( 0 ) = ( 2 e 2 e + 1 ) ( 2 e ) = 4 e 2 e + 2 \begin{aligned} \lim_{x\to0} \frac{g(g(x)) - g(e)}{x} &= \lim_{x\to0}\frac{(g\circ g)(x) - (g\circ g)(0)}{x-0} \\ &= (g\circ g)'(0) \\ &= g'(g(0))\cdot g'(0) \\ &= (2e^{2e+1})\cdot (2e) \\ &= \boxed{4e^{2e+2}} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...